2014
DOI: 10.1371/journal.pone.0102755
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Local Dengue Transmission in Guangzhou, China, through the Influence of Imported Cases, Mosquito Density and Climate Variability

Abstract: IntroductionEach year there are approximately 390 million dengue infections worldwide. Weather variables have a significant impact on the transmission of Dengue Fever (DF), a mosquito borne viral disease. DF in mainland China is characterized as an imported disease. Hence it is necessary to explore the roles of imported cases, mosquito density and climate variability in dengue transmission in China. The study was to identify the relationship between dengue occurrence and possible risk factors and to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 43 publications
(53 reference statements)
5
87
1
1
Order By: Relevance
“…However, although precipitation appears to be a key driver of the shorter-term changes (this study), urban landscape features, such as recently constructed artificial lakes in Guangzhou, appear to be key drivers of longerterm trends (21). As in other dengue epidemic areas (11,22,23), we find a strong link between dengue incidence and density of Aedes mosquitoes, the vectors of dengue. These findings support the utility of vector population control through, for example, pesticides, Wolbachia bacteria infection of mosquitoes, or habitat measures, for reducing the intensity of dengue outbreaks (24,25).…”
Section: Significancementioning
confidence: 45%
See 1 more Smart Citation
“…However, although precipitation appears to be a key driver of the shorter-term changes (this study), urban landscape features, such as recently constructed artificial lakes in Guangzhou, appear to be key drivers of longerterm trends (21). As in other dengue epidemic areas (11,22,23), we find a strong link between dengue incidence and density of Aedes mosquitoes, the vectors of dengue. These findings support the utility of vector population control through, for example, pesticides, Wolbachia bacteria infection of mosquitoes, or habitat measures, for reducing the intensity of dengue outbreaks (24,25).…”
Section: Significancementioning
confidence: 45%
“…Daily records of human dengue cases from 2005 to 2015 were obtained from the China National Notifiable Disease Surveillance System. All human dengue cases were diagnosed according to the diagnostic criteria for Dengue Fever (WS216-2008) enacted by Chinese Ministry of Health (11,33). The information on individual dengue cases included whether they were local or imported (local cases were defined as dengue cases where infection most likely occurred due to local transmission as there was no documentation of travel to dengue-endemic foreign regions; imported cases were those where infection most likely occurred outside of China).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the multiple introductions, dengue outbreaks occurred in epidemic seasons in Southern China in the context of suitable weather conditions [42]. Population movement at finer spatial scales contributed to the epidemic foci expansion, and may contribute dengue transmission from one epidemic city to another one within China [6].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on its epidemiologic features and some influential factors in the regions with high incidence [6][7][8]. Recent studies have revealed that all dengue epidemics in China are caused by imported dengue cases [9][10][11]. In addition to the direct role of imported cases, the epidemics are also attributed to natural factors that affect the breeding and survival of the Aedes mosquitoes, such as climatic (temperature, humidity), vegetative, and socio-economic factors that affect human-mosquito contact, such as population density, population mobility, economic development, and living conditions of a specific city [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%